2019
DOI: 10.1371/journal.pone.0226105
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of transformed goat primary cells by expression of simian virus 40 large T antigen for orf virus propagations

Abstract: Due to the limited host range of orf virus (ORFV), primary cells derived from its natural hosts, such as goats and sheep, are recommended for isolation and propagation of wild type ORFV. This situation limits the option for the study of virus-host interaction during ORFV infection since primary cells only support a few numbers of passages. SV40 T antigen is a viral oncoprotein that can abrogate replicative senescence, leading to an extended life span of cells. In this study, the transformation of two goat prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…The earliest method for immortalizing cell lines via inactivation or bypass of the p53/p16/Rb stress response has been transformation with viral genes. A notable example is the simian virus 40 (SV40) large T-antigen (TAg), which binds to and inactivates p53/Rb as well as other tumor suppressor factors in a number of species and organ types [ 28 , 29 , 30 ]. In the wild, SV40 is thought to infect senescent kidney epithelial cells in Rhesus macaques; here, TAg reactivates the host cell in order to promote replication of the SV40 virion [ 31 ].…”
Section: Methods For Establishing Immortal Cell Linesmentioning
confidence: 99%
“…The earliest method for immortalizing cell lines via inactivation or bypass of the p53/p16/Rb stress response has been transformation with viral genes. A notable example is the simian virus 40 (SV40) large T-antigen (TAg), which binds to and inactivates p53/Rb as well as other tumor suppressor factors in a number of species and organ types [ 28 , 29 , 30 ]. In the wild, SV40 is thought to infect senescent kidney epithelial cells in Rhesus macaques; here, TAg reactivates the host cell in order to promote replication of the SV40 virion [ 31 ].…”
Section: Methods For Establishing Immortal Cell Linesmentioning
confidence: 99%
“…Human embryonic kidney 293T cell (293T), DGCR8 knockdown (KD) 293T cell, human lung adenocarcinoma A549 cell, immortalized goat testis cell (GTT) [21] and Madin‐Darby Canine Kidney cells (MDCK) were cultured in Dulbecco's modified eagle medium (DMEM) supplemented with 10% FBS (Gibco BRL, Life Technologies Corporation, Carlsbad, CA, USA) and 1% of penicillin‐streptomycin. Cells were maintained at 37 °C with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant ORFV expressing eGFP (ORFV‐eGFP) was described in the previous study [7]. In this study, cells were infected with ORFV‐eGFP at the indicated multiplicity of infection (MOI) for 1 h, and were subsequently cultured in DMEM supplemented with 2.5% FBS for 24 or 48 h. Viral yield was determined by plaque assay in GTT cells [21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transferred membranes were blocked in 5% skimmed milk, followed by immunoblotting with specific antibodies against target proteins. In particular, the antibodies (and corresponding dilutions) were the following: FLAG antibody (1 : 2000) (F7425; Sigma-Aldrich), PKR antibody (1 : 1000) (ab32052; Abcam, Cambridge, UK), phosphor-PKR (PKR-p) antibody (1 : 1000) (ab32036; Abcam), ADAR1 antibody (1 : 500) (sc-73408; Santa Cruz Biotechnology), actin antibody (1 : 5000) (NB600-501; Novus Biologicals, Centennial, CO, USA), actin of N. benthamiana antibody (1 : 5000) [32], EGFP antibody (1 : 2000) (YH80005; Yao-Hong Biotechnology, New Taipei City, Taiwan), and F1L antibody (1 : 2000) [33]. Secondary antibody-conjugated horseradish peroxidase (HRP) was diluted in 5% skin milk and incubated with membranes for 1 h at room temperature.…”
Section: Western Blottingmentioning
confidence: 99%